Determinants of Visual Inspection with Acetic Acid (IVA) Test Utilization based on Risk Factors Group - Aina Mabrukah; Ayun Sriatmi; Rani Tiyas Budiyanti (JURNAL INFO KESEHATAN, 2025)
The Visual Inspection with Acetic Acid (IVA) test aims to diagnose early so that it can speed up treatment, reduce morbidity and mortality in women due to cervical cancer. IVA test coverage in Magelang district has not reached the target, especially in the at-risk group. The study aims to see the difference in utilization of IVA services in groups of mothers who are divided into at-risk and non-risk groups. The method used was quantitative method that uses a comparative design. The study population was all mothers aged 30-50 years in Magelang district. Respondents of each group were 68 people determined by proportional sampling technique. Univariate analysis with frequency distribution table and bivariate analysis with Mann-Whitney test because the data was not normally distributed. There was no difference in the utilization of IVA services between the at-risk and non-risk groups (p=0.205). However, it was statistically proven that the at-risk group had a better level of knowledge, attitude, and lifestyle, and felt more vulnerable and needed an IVA test than the non-risk group. Meanwhile, the non-risk group had better perceptions of accessibility and health worker support than the risk group. Risk factor mapping at the Health Center level needs to be done to develop needs-based interventions to increase IVA coverage.